Frontispiece: An Unprecedented Blue Chromophore Found in Nature using a "Chemistry First" and Molecular Networking Approach: Discovery of Dactylocyanines A–H. Issue 58 (17th October 2017) - Bonneau, Natacha; Chen, Guanming; Lachkar, David; Boufridi, Asmaa; Gallard, Jean‐François; Retailleau, Pascal; Petek, Sylvain; Debitus, Cécile; Evanno, Laurent; Beniddir, Mehdi A.; Poupon, Erwan
Abstract : Recently, molecular networking has emerged as a promising computer‐based approach to visualize and organize MS/MS data sets arising from complex mixtures. The success of this strategy relies on the availability and quality of MS/MS data for the annotation of the networks. In this study, MS/MS spectra of a well‐tailored phishing probe were incorporated into Dactylospongia metachromia crude extract network for annotating and matching structurally related natural substances. This "Chemistry First" approach allowed characterizing for the first time in Nature the blue zwitterionic quinonoid chromophore. For more information see the Full Paper by M. A. Beniddir et al. onpage 14454 ff.